The Role Of Financial Performance As A Mediator Of The Effects Of Financial Flexibility, Capital Structure, And Environmental Social Governance On Firm Value, Moderated By Investment Efficiency (Study Of Mining Companies Listed On The Indonesia Stock Exch (Architecture Image Studies, 2026)
This study aims to examine and assess the influence of financial flexibility, capital structure, and environmental social governance on financial performance and firm value, as well as the influence of financial performance on firm value. Furthermore, this study examines the role of investment efficiency in moderating the influence of financial flexibility on financial performance, and examines the role of financial performance in mediating the influence of financial flexibility, capital structure, and environmental social governance on firm value. This study uses an ex post facto approach. The population comprised all mining companies listed on the Indonesia Stock Exchange. Purposive sampling was used, with a sample size of nine companies and 90 observations. The research model is structural. The analytical method used in this study is SEM-PLS (Partial Least Squares). The results of the study show that as follows: (1) financial flexibility has a positive and significant effect on financial performance, (2) capital structure has a negative but not significant effect on financial performance, (3) environmental social governance has a positive and significant effect on financial performance, (4) financial flexibility has a negative but not significant effect on company value, (5) capital structure has a negative and significant effect on company value, (6) environmental social governance has a positive but not significant effect on company value, (7) financial performance has a positive and significant effect on company value, (8) investment efficiency has a negative but not significant effect in moderating the effect of financial flexibility on financial performance, (9) financial performance has a positive and significant effect in mediating the effect of financial flexibility on company value, (10) financial performance has a negative but not significant effect in mediating the effect of capital structure on company value, and (10) financial performance has a positive and significant effect in mediating the effect of environmental social governance on company value.